Workability and well-being at work among cut-to-length forest machine operators - Kymäläinen, Heli (Array, 2021)
This study assessed the situation of Finnish cut-to-length (CTL) machine operators" work well-being with workability index (WAI), investigated CTL machine operators" lifestyle habits, and collected operators" good practices to maintain and promote well-being and vitality at work. A questionnaire was conducted in electronic form, including questions concerning background information, work environment, work organisation, well-being at work and free time, and workability index. Mean WAI among respondents was 42.2 points (max. 49) falling into the rank "good", while the current workability compared with the lifetime best was 8.2 (range 0–10). WAI was strongly impacted by age (p<0.000), the score declined during ageing, and standard deviation grew. The results were in line with previous WAI studies. Statistic differences were found between youngest age group (age≤25) versus all others. Compared to other studies and occupational groups, CTL machine operators’ WAI was average. Operators revered independent nature of work and forest as a working environment, thus promoting and maintaining well-being at work. Furthermore, breaks during work shift, with or without physical exercise, was recognised to ensure and retain vitality and concentration at work.